2019
DOI: 10.1007/jhep10(2019)268
|View full text |Cite
|
Sign up to set email alerts
|

Propagator identities, holographic conformal blocks, and higher-point AdS diagrams

Abstract: Conformal blocks are the fundamental, theory-independent building blocks in any CFT, so it is important to understand their holographic representation in the context of AdS/CFT. We describe how to systematically extract the holographic objects which compute higherpoint global (scalar) conformal blocks in arbitrary spacetime dimensions, extending the result for the four-point block, known in the literature as a geodesic Witten diagram, to five-and six-point blocks. The main new tools which allow us to obtain su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 123 publications
(334 reference statements)
1
98
0
Order By: Relevance
“…These results are also consistent with those of [72,73] which used geodesic Witten diagrams [76]. Now we turn to the crossed channel decomposition.…”
Section: Warmup: Five-point Treesupporting
confidence: 86%
See 2 more Smart Citations
“…These results are also consistent with those of [72,73] which used geodesic Witten diagrams [76]. Now we turn to the crossed channel decomposition.…”
Section: Warmup: Five-point Treesupporting
confidence: 86%
“…There have been a few studies of higher-point correlators, e.g. [71][72][73]77] but they have received much less focus than four-point functions. However, as we study higher-loop, fourpoint correlators in AdS/CFT they inevitably appear when cutting certain Witten diagrams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[54]). Geodesic diagram representations have also been obtained for the same five-point block in general spacetime dimensions [55], as well as for the d-dimensional six-point scalar conformal block involving scalar exchanges in a different channel called the OPE channel [56].…”
Section: Jhep05(2020)120mentioning
confidence: 99%
“…3 The study of the scattering amplitudes of gauge theories and gravity has revealed remarkably simple structures in flat space and has led to menagerie of basis such as twistors and geometric formulations like the amplituhedron [15][16][17][18][19]. Additionally, in the last several years we have witnessed inspiring representations which have helped in showing similarities between scattering amplitudes in flat space and their AdS counterparts [9,[20][21][22][23][24][25][26][27][28][29][30][31][32][33]. One related insight has come out of the recent investigation of holographic momentum space which indicates an interesting connection between momentum space Witten diagrams and flat space scattering amplitudes.…”
Section: Introductionmentioning
confidence: 99%